2022
DOI: 10.3389/fpsyt.2022.839656
|View full text |Cite
|
Sign up to set email alerts
|

Viral Anxiety Mediates the Influence of Intolerance of Uncertainty on Adherence to Physical Distancing Among Healthcare Workers in COVID-19 Pandemic

Abstract: IntroductionThe aims of this study were to examine the mediation effect of viral anxiety of healthcare workers on the influence of their intolerance of uncertainty on the adherence to physical distancing during the COVID-19 pandemic.MethodsAn online survey was conducted among 329 healthcare workers (female: 81.4%, nursing professionals: 59.0%, and shift workers: 22.3%) on November 29, 2021. Participants responded to questionnaires on adherence to physical distancing, health beliefs, and perceived social norms,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 7 publications
(22 citation statements)
references
References 48 publications
4
18
0
Order By: Relevance
“…We observed that nursing students’ adherence to physical distancing was associated with their viral anxiety measured with a viral epidemic-specific rating scale (Stress and Anxiety to Viral Epidemics-6 items [SAVE-6] [ 21 ]) [ 22 ]. Additionally, among healthcare workers, we also observed similar results [ 23 ]. We can speculate that an individual’s elevated social distancing phobia may be related to their adherence to physical distancing, and we can hypothesize that viral anxiety might be associated with social distancing phobia among the general population.…”
Section: Introductionsupporting
confidence: 85%
See 1 more Smart Citation
“…We observed that nursing students’ adherence to physical distancing was associated with their viral anxiety measured with a viral epidemic-specific rating scale (Stress and Anxiety to Viral Epidemics-6 items [SAVE-6] [ 21 ]) [ 22 ]. Additionally, among healthcare workers, we also observed similar results [ 23 ]. We can speculate that an individual’s elevated social distancing phobia may be related to their adherence to physical distancing, and we can hypothesize that viral anxiety might be associated with social distancing phobia among the general population.…”
Section: Introductionsupporting
confidence: 85%
“…22 Additionally, among healthcare workers, we also observed similar results. 23 We can speculate that an individual's elevated social distancing phobia may be related to their adherence to physical distancing, and we can hypothesize that viral anxiety might be associated with social distancing phobia among the general population.…”
Section: Intolerance Of Uncertainty Viral Anxiety and Physical Distan...mentioning
confidence: 96%
“…This pattern made them adhere to the physical distancing policy more. 21 This study also observed that firefighters' pandemic grief response and intolerance of uncertainty could distribute CO-VID-related hypochondriacal responses. Pandemic grief response influenced their viral anxiety, reassurance-seeking behavior, and preoccupation with the virus.…”
Section: Discussionsupporting
confidence: 55%
“…35 Among healthcare workers, it was reported that intolerance of uncertainty was one of the factors for psycho-logical stress, contributing to adherence to the physical distancing policy. 21 Firefighters' intolerance of uncertainty influences their hypochondriacal responses to coronavirus, and resultantly it may act as a double-edged sword. Preoccupation with coronavirus makes them adhere to physical distancing and is a preventive measure for their health status and those they care for.…”
Section: Discussionmentioning
confidence: 99%
“…The practice entails staying at least two meters away from others in crowded public places, avoiding large crowds, and minimizing non-essential travel [ 2 ]. This policy was helpful in slowing down the spread of the virus, reducing the infection or mortality rates from the virus, and reducing the burden placed on healthcare systems [ 3 ]. However, the term physical distancing was changed from social distancing [ 4 ], because the latter insinuates being ignored, unwelcome, left alone, and even being excluded from society.…”
Section: Introductionmentioning
confidence: 99%